VD_FINDINFO AI 168/10 - 541/2011 vom 30. November 2011 - VD Tribunal cantonal (2011)
RENTE D'INVALIDITÉ, ÉVALUATION DE L'INVALIDITÉ, RENTE TEMPORAIRE | 28 al. 2 LAI, 4 al. 1 LAI, 17 al. 1 LPGA, 8 al. 1 LPGA